The Development of Quizizz-Based Interactive Design using Whole-Part-Whole Model for Teaching English Vocational School for Culinary Arts Department - Rosyida, Amrina; Sujana, I Made; Apgrianto, Kurniawan; Melani, Boniesta Zulandha (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research is a Research and Development study aimed at developing game-based English language learning tailored to the needs of students in the culinary field, utilizing ESP (English for Specific Purposes) and the Whole-Part-Whole model. The data were analyzed using both qualitative and quantitative descriptive methods. Qualitative data were generated during the Analysis phase of the ADDIE research procedure, which served as material for content development. Quantitative data were obtained from expert judgment. The data analysis process, which included document analysis and interviews, identified several student needs related to English language learning. The results of this study were as follows: In the first stage (whole), materials were presented along with interactive quizzes through Quizizz. In the second stage (part), detailed materials were displayed, covering definitions, social functions, text structure, and linguistic features of procedural texts. In the third stage (whole), students were assigned to create their procedural texts, both orally and in writing, using Quizizz. The average percentage of student perception was 92.03%, indicating that the module implemented in class is highly suitable. The average rate of expert judgment reached 95.83%, with an interpretation score of very suitable. Thus, developing an interactive quiz-based design for teaching English in culinary vocational schools at SMK N 4 Mataram was deemed very appropriate for use in the teaching and learning process.